Applying structural equation model to study the critical risks in business intelligence and analytical system implementation in Indian retail. (2018) - Rajesh, K.; Saravanan, D.
In order to reduce the failure rate of business intelligence and analytical system (BIAS) projects in Indian retail, project managers need to analyse and understand the impact of a risk factor on BIAS implementation. The main objective of this paper is to identify the key risk factors solely or primarily for the Indian retail sector. A theoretical model is developed that explains the risk factors which may impact the success of BIAS implementation. Using the SEM, it is found that 40% of the variations in BIAS implementation success can be explained with the help of the model suggested in the research study. The findings from this paper can provide a greater understanding of BIAS implementations. Researchers, practicing managers, and those seeking to implement BIAS in the retail organisation can also use the findings of this study as a vehicle for improving BIAS implementation success in the retail sector.